Desenvolvimento e verificação de um sistema computacional para cálculo da adubação/fertirrigação de melão e melancia - Paula, José Aluísio de Araújo (Universidade Federal Rural do Semi-Árido, 2007)
The objective of the work was to develop a computational system to calculate levels and portioning out of nitrogen, phosphorus and potassium for the foundation manuring and fertirrigation of melon and watermelon and to validate it with experimental dates. A system was elaborated following the methodologies used in the models of FERTICALC and of other authors, being used the correction factors for use of the nutrients N, P and K, as in foundation manuring (conventional) as in manuring fertirrigation to determine the doses of the nutrients (N, P and K). The totals exported in N P K they are related to the longed productivity, so much for date of total production, as for date of commercial production, for the nutrients of each studied culture. To evaluate the system efficiency, it was assumed medium dates common to the cultivated areas with melon and watermelon, besides the date that correspond to the areas of the experiments with melon and with watermelon. It was adopted as productivity longed for melon and watermelon, respectively, 36 and 28 Mg ha-1. The work in field was accomplished in the area producing of melon and watermelon located in Assú/Mossoró Agricultural pole. For the experiment with melon, it was used the scheming in casualizad blocks with three repetitions and combination of the dose of N (42, 84 and 126 kg.ha-1) and of K (106, 212 and 322 kg.ha-1) being, N2 and K2 the doses would intermediate, more three additional treatments(N0K0, N0K2 and N2K0) arranged in the factorial outline 3 x 3 + 3. For the experiment with watermelon adopted the same experimental scheming, with combination of three doses of nitrogen, N1 (45 kg ha-1), N2 (91 kg ha-1) and N3 (136 kg ha-1) and three potassium doses, K1 (78 kg ha-1), K2 (156 kg ha-1) and K3 (234 kg ha-1), besides two additional treatments: (N0K2 and N2K0), being N2 and K2 the dose recommended for fertilization and N0 and K0 without the application N and K, respectively. To measure the efficiency of the system, it was used the Agreement Index d . The coefficients of determination of the straight line (R2) of the functions productivity vs. export of nutrients was high, so much for the curves of the watermelon, as for the curves of the melon. The productivity zone for which the functions medium productivity vs. nutrients export, as for melon, as for watermelon they embrace all found situations in the producing areas. The applicability of the software was satisfactory, since it answers with efficiency the conditions imposed in system for they definition of the amounts applied of N, P and K and they distribution week/daily for the fertilizers. The melon and the watermelon answered the doses of N and K, it obtaining maximum productivity, respectively, for the maximum doses, of applied nitrogen in fertirrigação, different from the potassium that didn't affect the productivity of the culture, and doses of N and applied K in fertirrigation. The application of the index d it revealed high agreement among the values obtained in field and the simulate by the system, for the total absorption of nutrients of N and K, so much for watermelon, as for the melon
Development and verification of a computational system for calculation of the melon and watermelon manuring/fertirrigation
Keywords: Citrullus lanatus; Cucumis melo; Sistema Computacional; Nutrientes; Citrullus lanatus; Cucumis melo; Computational System; Nutritious; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA